Financing options and productivity of micro- and small-sized firms in Cross River State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examined the impact of financing options (internal, external, and debt-equity financing) on firm productivity using the Ordinary Least Squares (OLS) econometric approach with robust standard errors. Data was obtained through a face-to-face survey of 134 Micro and Small Enterprises (MSEs) in sectors such as commerce, manufacturing, services, agriculture, education, and health conducted in Calabar, Cross River State. The result showed that the correlation between the variables is neither perfect nor zero, and may be used for regressionanalysis. Among the financing choices examined, internal financing had a significant negative effect on firm productivity in Cross River State, Nigeria. Specifically, an increase in internal finance of the firm by one per cent results in a 25 per cent decrease in firm’s productivity. Secondly, the study discovered that debt-equity financing had a significantly positive effect on productivity of firms in Cross River State, Nigeria. Specifically, debt-equity financing improved firm productivity by 12 per cent. Thus, debt-equity financing as against internal or external financing produced more robust result in its impact on firm productivity. Based on these findings, the study recommended that managers of firms should make financing decisions in such a manner as to spread the risk and minimize cost of funds such that their productivity and profitability is not adversely affected.
Keywords: Financing choices; Productivity; Small and Medium-Scale Enterprises JEL Classification; D24; G23; G21